Logistical challenges faced by Civil Defense in the 2023 São Sebastião disaster - Barino, Raphael Sepulveda; Lira, Viviane Cardoso Pereira; Cunha, Luiza Ribeiro Alves; Junior, Irineu de Brito [UNESP] (FapUNIFESP (SciELO), 2024)
Paper aims: This case study analyzes the logistics challenges faced by the Civil Defense in responding to the disaster that hit São Sebastião City, in February 2023. Originality: The study contrasts theory with practice by analyzing a real case considering the concepts of humanitarian logistics and disasters. Research method: This research is classified as qualitative, applied, and exploratory, based on an inductive logical framework, using the case study method. It examines a variety of information sources, including bulletins, reports, municipal data, media content, and information from disaster management-related entities’ websites. Data interpretation was conducted continuously, starting from the collection phase, and was detailed and analyzed using a crisis management model prevalent in the literature. Main findings: The results offer practical lessons for professionals and contribute to enhancing disaster preparedness policies and response manuals, emphasizing the importance of coordination among response agencies, the need for effective communication with affected community stakeholders, and the mobilization of logistical resources for the distribution of relief supplies. Implications for theory and practice: This research addresses the necessity of documenting logistics challenges in the face of disaster events, contributing to knowledge management within entities. It also maps the operational bottlenecks encountered in disaster coordination.
Keywords: Civil Defense; Climate Events; Disaster Response; Humanitarian Logistics; Socio-Environmental Vulnerability